Systemic Family Music Therapy: Sound-musical practices in the strengthening of post-adoption family ties - Garcia, Gabriely (2021)
The Systemic Family Music Therapy (SFMT) is an underexplored approach in Brazil, and it aims to use music and its elements to promote the improvement of the family system and family relationships. Sometimes, the issues to be worked on in family therapy are complex and difficult to express in words and, in this context, musical practices can favor the expression of these contents. This research aims to describe the contributions of sound-musical practices in strengthening post-adoption family ties from the perspective of the SFMT. It is characterized as qualitative and exploratory research. It reports six interventions carried out with a post-adoption family, in Curitiba, Paraná, Brazil. It identifies as contributions of the sound-musical practices experienced: changes in the patterns of family relationships; integration between family members in shared sound-music making; space-time opportunity to listen to family members. It concludes that the interventions made it possible to observe significant changes in the listening and posture of family members, aspects that contributed to the family dynamics, as well as providing opportunities to expand the knowledge about SFMT.